Procrastinating during thesis time: factors than obstruct its completion in undergraduate students - Genise, Nicolás (2024)
The completion of the Final Integrative Project (FIP) or thesis is a significant milestone in the academic career of university students. This process represents the integration of skills built throughout their educational career and requires facing various challenges. However, it is observed that many students face obstacles that make it difficult to complete this work, which has led to high rates of delays and dropouts at various educational levels. The purpose of this research is to explore and characterize the personal and institutional factors that contribute to the delay and postponement in the completion of the Integrative Final Projects of the students of the Bachelor’s Degree in Psychopedagogy (curriculum complementation cycle - Distance Modality). In this study, a mixed approach was used, combining quantitative and qualitative methods, adopting a descriptive and cross-sectional design. The questionnaire “The Writing Process Questionnaire” was applied, an instrument developed by Lonka et al., (2014) and translated into Spanish by Cerrato Lara et al., (2017) to a sample of 122 students. Based on the data analysis, it was concluded that institutional factors affect and hinder students’ completion of the TFI, surpassing the influence that personal factors may have, causing students to experience high levels of blockage, exhaustion and anxiety, giving rise to procrastination.